Cenozoic mountain building and topographic evolution in Western Europe: impact of billions of years of lithosphere evolution and plate kinematics - Mouthereau Frédéric (EDP Sciences, 2021)
The architecture and tectono-magmatic evolution of the lithosphere of Europe are the result of a succession of subduction, rifting and inputs from plumes that have modified the lithospheric mantle since the Neoproterozoic (750–500 Ma). These events gave birth to contrasting crust-mantle and lithosphere-asthenosphere mechanical coupling between strong, viscous, thick, cold, depleted mantle of the Archean lithosphere of the West African Craton and the East European Craton, and the weak, low viscous, thin, hot and less depleted mantle of the Phanerozoic lithosphere of Central Europe. These differences were long-lived and explain the first-order present-day stresses and topography as well as the styles of orogenic deformation. The lack of thermal relaxation needed to maintain rheological contrasts over several hundreds of millions of years requires high mantle heat flux below Central Europe since at least the last 300 Ma. A combination of edge-driven convection on craton margins and asthenospheric flow triggered by rift propagation during the Atlantic and Tethys rifting is suggested to be the main source of heat. The topography of Central Europe remained in part dynamically supported during most of the Mesozoic thinning in line with the long-term stability of thermal-mechanical structure of the lithosphere. Timing and rates of exhumation recorded across Western Europe during convergence indicate that an additional control by the architecture of Mesozoic rifted margins is required. By 50 Ma the acceleration of orogenic exhumation, from the High Atlas to the Pyrenees, occurred synchronously with the onset of extension and magmatism in the West European Rift. Extension marks the onset of distinct orogenic evolution between Western Europe (Iberia) and the Alps (Adria) in the east, heralding the opening of the Western Mediterranean. A major kinematic re-organisation occurred triggering the involvement of more buoyant and thicker portions of rifted margins resulting in widespread orogenic growth. We conclude that conceptual models of collision require to better account for the thermo-magmatic evolution of the continental lithosphere, especially the original architecture and composition of its mantle, as well as the precise knowledge of the architecture of the rifted margins to explain the timing and rates of orogenic topography.